Memory in Caryl Phillips’s novel Crossing the River (1993) - doi: 10.4025/actascilangcult.v33i1.8830 - Susanne Pichler (Acta Scientiarum. Language and Culture, 2011)
This article explores the themes of memory and remembering as well as the relationship between memory and diaspora in Caryl Phillips’s prize-winning 1993 novel Crossing the River. While the first part of the paper discusses theoretical and methodological issues in memory studies, the second part deals with an analysis and interpretation of the novel, which, it is hoped, provides interesting insights into Phillips’s multifaceted use of (the concept of) memory and what it entails.